Gereja yang Kudus bagi Para Pendosa: Memaknai Panggilan menuju Kekudusan dalam Gereja - Derian, Mikhael Varian Toar (Institutum Ioannis Mariae Vianney Surabayanum, 2024)
The Council of Nicaea Constantinople in 325-381 established the dogma of the one, holy, catholic and apostolic Church. Of these four notes of the Church, the holiness of the Church is perhaps the most hotly debated topic today. The reason for this is due to the revealed scandals in the Catholic Church in the last few decades. Moreover, the perpetrators are people who are within the highest levels of hierarchy the Church itself. Apparently, mortal sin does not escape the lay people, priests, religious and even bishops. If holiness means a state of sinlessness, then how can we understand that the Church is holy but at the same time its members sin? Is this teaching of the Council of Nicea-Constantinople still relevant in the 21st century? In this paper, the author wants to deepen the dogma of the holiness of the Church by studying from sources such as the Holy Scriptures, the Fathers of the Church, and Magisterial Documents about where the Church derives its holiness from and for what purpose it is holy. By doing so, the dogma of the holy Church will hopefully be better understood by today's readers.